2010
DOI: 10.1186/1471-2407-10-76
|View full text |Cite
|
Sign up to set email alerts
|

HAX-1 overexpression, splicing and cellular localization in tumors

Abstract: BackgroundHAX-1 has been described as a protein potentially involved in carcinogenesis and especially metastasis. Its involvement in regulation of apoptosis and cell migration along with some data indicating its overexpression in cancer cell lines and tumors suggests that HAX-1 may play a role in neoplastic transformation. Here we present the first systematic analysis of HAX-1 expression in several solid tumors.MethodsUsing quantitative RT-PCR, we have determined the mRNA levels of HAX1 splice variant I in sev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
75
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 64 publications
(78 citation statements)
references
References 29 publications
(52 reference statements)
2
75
1
Order By: Relevance
“…Variants V-VIII are expressed at very low levels and contain frameshifts that change the protein sequence (Lees et al, 2008;Trebinska et al, 2010); therefore, only variants I-IV were analyzed in this study ( Fig. 2A, B).…”
Section: Hax-1-dcp1 Colocalization Is Hard To Disruptmentioning
confidence: 99%
“…Variants V-VIII are expressed at very low levels and contain frameshifts that change the protein sequence (Lees et al, 2008;Trebinska et al, 2010); therefore, only variants I-IV were analyzed in this study ( Fig. 2A, B).…”
Section: Hax-1-dcp1 Colocalization Is Hard To Disruptmentioning
confidence: 99%
“…Patients with autosomal recessive forms of severe congenital neutropenia (SCN) or Kostmann disease, a condition associated with a maturation arrest in the bone marrow and a lack of mature neutrophils in peripheral blood, displayed mental retardation, attention deficit, epilepsy, and speech and gross motor retardation [13,17]. There is also emerging evidence that HAX-1 is overexpressed in various human premalignant epithelial dysplasic and oral squamous cell carcinomas [18] as well as in breast cancer tissues [19]. Therefore, the abnormally high levels of HAX-1 that are associated with cancer may be a consequence of HAX-1 0 s function as an anti-apoptotic protein.…”
Section: Introductionmentioning
confidence: 98%
“…Studies indicate that variant II and variant III levels are reproducibly higher in tumors rather than normal tissues. 19 In addition, monoallelic loss of FBXO25 stabilizes HAX-1 in tumor cells. 26 Mechanisms were developed in tumor cells to overexpress the HAX-1.…”
Section: Discussionmentioning
confidence: 99%
“…17 In BC, previous studies have indicated that overexpression of HAX-1 promotes the development of cancers via improving their survival and is associated with the tumor size, stage, and grade of the disease. 18,19 The HAX-1 in cancers therefore has been reported as the new target for cancer therapy. 20 However, since the role of HAX-1 in BC treatment remains unclear, the aim of this study was thus to investigate the relationship between the chemoresistance and HAX-1 in BC.…”
Section: Introductionmentioning
confidence: 99%